Incidence and characteristics of drowning in Sweden during a 15-year period. (May 2021) - Claesson, A.; Krig, A.; Jonsson, M.; Ringh, M.; Svensson, L.; Forsberg, S.; Nord, A.; Nordberg, P.; Olausson, M.; Jacobsson, A.; Nilsson, L.; Hollenberg, J.
Abstract: Aim: Drowning is a global health problem and deeper knowledge about the extent and causes is of utmost importance for implementing preventative actions. The aim of this study was to describe the incidence and characteristics of drowning in Sweden over time, including both non-fatal and fatal cases. Methods: All cases identified as drowning (ICD-10 coding) at a national level in Sweden between 2003–2017 were collected. Three sources of data from the Swedish National Board of Health and Welfare were extracted via the Cause of Death Register and the National Patient Register. Results: Over 15 years, a total of 6609 cases occurred, resulting in an annual incidence of 4.66 per 100 000. The median age was 49 years (IQR 23–67) and 67% were males. Non-fatal drownings represented 51% (n = 3363), with an overall non-fatal to fatal ratio of 1:1, this being 8:1 for children (0–17 years of age). Non-fatal cases were more often female (36% vs. 30%; p < 0.001), younger 30 (IQR 10−56) vs. 60 (IQR: 45−72) (p < 0.001) and of unintentional nature (81% vs. 55%; p < 0.001). The overall incidence decreased over time from 5.6 to 4.1 per 100 000 (p < 0.001). The highest rate of 30-day survival was found in females 0−17 years (94%, 95% CI 91.1–95.5) and the lowest in males >66 years (28.7%, 95% CI 26.2–31.2). Although the incidence in children 0–4 years increased from 7.4 to 8.1 per 100 000 (p < 0.001), they demonstrated the highest non-fatal to fatal ratio (13:1). Conclusion: Drowning is declining but remains a consistent and underestimated public-health problem. Non-fatal drowning cases represent about half of the burden and characteristics differ from fatal drowning cases, being younger, more often female and of unintentional nature.